BUILDING SUSTAINABLE WASTE MANAGEMENT BASED ON ENVIRONMENTALLY FRIENDLY BEHAVIOR IN HEALTHCARE INDUSTRY: A SYSTEMATIC REVIEW - Viqi Ardaniah (Jurnal Riset Akuntansi Dan Bisnis Airlangga, 2022)
Establishing sustainable waste management in healthcare industries is challenging as the social, economy, environmental dimension in the sustainability needs to be complied. However, prior studies have proposed indicators to build the sustainable waste management without addressing a systematic manner leading to bias and considering the environmental dimension to drive stakeholder’s behavior. This study aimed to determine how environmentally friendly behavior affects the sustainable waste management in the healthcare industries. There were 874 articles collected from the databases consisting of PubMed, Sciencedirect, Scopus, SAGE and Ebscohost after removing the duplicates and 8 articles claimed to meet the inclusion criteria. The environmentally friendly behavior is driven by stakeholders’ consciousness towards environmental practices, strong belief, awareness, knowledge and perception. The behavior needs to be reinforced by regulations and institutions and improved by training and education in order to develop the sustainable waste management. Theoretically, this study contributes to sustainable waste management by addressing more on environmentally friendly behaviors of all actors. In managerial implication, this study also offers considerations for firms on the areas which need to be improved to gain sustainable practices